Snow gliding susceptibility: the Monterosa Ski resort, NW Italian Alps. Issue 1 (4th November 2016) - Maggioni, M.; Godone, D.; Höller, P.; Oppi, L.; Stanchi, S.; Frigo, B.; Freppaz, M.
ABSTRACT: Snow gliding, though a slow process, should be considered as important as the faster snow avalanche flows, as it can similarly produce severe damage to buildings and infrastructure. Snow gliding depends on snowpack properties, land cover and terrain parameters. Among these driving factors, in this work, we focus on stationary factors, that is, those that are considered features related to terrain and land cover, in particular those that could be derived from a Digital Elevation Model or land use/cover maps: slope angle, aspect, roughness and land cover. We propose a geographical information system-based procedure to create a snow gliding susceptibility index and to produce a related snow gliding susceptibility map. We tested this procedure in the Aosta Valley (NW Italian Alps), where the Monterosa Ski resort is located. The map covers an area of about 338 km 2 at a scale of 1:50, 000. The proposed procedure is seen as a valuable tool to help safety personnel at ski resorts as well as in other scenarios (e.g. road management) in the identification of areas most prone to snow gliding.